Gamification in Education and Business 2014
DOI: 10.1007/978-3-319-10208-5_32
|View full text |Cite
|
Sign up to set email alerts
|

Gamification-supported Exploration and Practicing for Automotive User Interfaces and Vehicle Functions

Abstract: When driving an unknown car, the interaction with its user interfaces and the operation of (comfort) vehicle functions can be very challenging and thus cause safety concerns. However, this problem can be overcome already with a short learning and practicing phase.For this reason, we analyze the potential of gamification for exploring and practicing the use of automotive user interfaces and vehicle functions. Based on the analysis of available examples, we have created a gamified automotive exploration and prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Small-scale studies that employ games, empower an understanding of complex social-technological systems performances, managing personal mobility, and individual behavior change in the automotive domain. Due to their capability for stirring sustainable motivation and strong commitment [108,109], games also promote sustainable urban mobility [110,111]. Moreover, Delphi (11/2002) is used as a constructor of future experts' scenarios, basing its predictions on differences and similarities in experts' knowledge collected via surveys [112][113][114][115][116].…”
Section: Landscape Overview Of Indiviual Groups Of Methods and Their mentioning
confidence: 99%
“…Small-scale studies that employ games, empower an understanding of complex social-technological systems performances, managing personal mobility, and individual behavior change in the automotive domain. Due to their capability for stirring sustainable motivation and strong commitment [108,109], games also promote sustainable urban mobility [110,111]. Moreover, Delphi (11/2002) is used as a constructor of future experts' scenarios, basing its predictions on differences and similarities in experts' knowledge collected via surveys [112][113][114][115][116].…”
Section: Landscape Overview Of Indiviual Groups Of Methods and Their mentioning
confidence: 99%
“…Previous studies showed that serious games and gamified learning methods have been particularly and successfully applied in different business fields [ 11 , 16 ] and in sectors where technologies and mobile applications are used, such as automotive manufacturing [ 18 ], occupational health settings including medicine, surgery and rehabilitation [ 19 , 20 ], sports (e.g., baseball, [ 21 ]) and in hazardous working sectors such as firefighting [ 22 ], construction [ 1 ] and mining [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different car manufacturers developed several Gamification mechanisms and embedded them in their models. Diewald et al [21] provided a comprehensive review of such applications. From Volkswagen's BlueMotion Roulette to Ford's SmartGauge with EcoGuide, passing through the Kia's ECOdynamics and Fiat's eco:Drive.…”
Section: Background and Related Workmentioning
confidence: 99%